APLIKASI ENZIM BROMELIN DARI KULIT NANAS UNTUK BUDIDAYA MINA PADI DI DESA SUNGAI BAKAR KECAMATAN BAJUIN KABUPATEN TANAH LAUT - Aminah; Bahrun; Rina Iskandar; Yulius Kisworo (Fakultas Pertanian UVAYA Banjarmasin, 2025)
Minapadi cultivation is a form of integrated fisheries farming that requires stable water quality so that rice and fish grow optimally. Community service aims to increase the knowledge of the people of Sungai Bakar Village in applying appropriate technology through the use of Bromelin enzymes from pineapple skin waste as a natural additive in fish and rice cultivation. This community service activity was carried out using a persuasive approach, direct interviews with the community, then identifying problems in the field. This Community Service Activity was carried out in Sungai Bakar Village, Bajuin District, Tanah Laut Regency. The stages used in this activity include location surveys, implementation of P2M activities and activity evaluation. The utilization of Bromelin enzymes from pineapple skin waste as a natural additive in mina padi cultivation has succeeded in increasing the knowledge of the Sungai Bakar Village community about appropriate technology.